2009
DOI: 10.1002/aqc.1085
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of benthic communities in the fjord‐like Bathurst Channel ecosystem, south‐western Tasmania, a globally anomalous estuarine protected area

Abstract: ABSTRACT1. Benthic assemblages in the fjord-like Bathurst Channel estuarine system, south-western Tasmania, vary over horizontal scales of 1-5 km and vertical scales of 1-10 m. Multivariate analysis indicated a total of eight major assemblages that characterize different sections and depths of the channel.2. Because tannins in the low-salinity surface water layer block light, foliose algae reach 5 m depth in the marine western region but do not penetrate below 1 m in the east. By contrast, sessile invertebrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…This idea is supported by Smith and Witman (1999) who observed elsewhere that highly diverse benthic patches are maintained by increased habitat biogenic complexity that enhances larval recruitment. Försterra (2009) describes the extraordinary occurrence of "deep-sea species" in the shallow depths of the fjords of Patagonia (e.g., Comau Fjord), a phenomenon that has also been reported in similar fjords in New Zealand (e.g., Grange et al, 1981) and Australia (Barrett and Edgar, 2010). Overall, the facilitative effects of habitat-forming species could be contributing to the maintenance of the diversity found 10-15 m depth in the Comau Fjord (Reise, 2002;Gili et al, 2006).…”
Section: Habitat-forming Species and The Marine Animal Forestsmentioning
confidence: 95%
See 1 more Smart Citation
“…This idea is supported by Smith and Witman (1999) who observed elsewhere that highly diverse benthic patches are maintained by increased habitat biogenic complexity that enhances larval recruitment. Försterra (2009) describes the extraordinary occurrence of "deep-sea species" in the shallow depths of the fjords of Patagonia (e.g., Comau Fjord), a phenomenon that has also been reported in similar fjords in New Zealand (e.g., Grange et al, 1981) and Australia (Barrett and Edgar, 2010). Overall, the facilitative effects of habitat-forming species could be contributing to the maintenance of the diversity found 10-15 m depth in the Comau Fjord (Reise, 2002;Gili et al, 2006).…”
Section: Habitat-forming Species and The Marine Animal Forestsmentioning
confidence: 95%
“…Species in this genus are very well adapted to low light and temperature regimes (Johansen, 2018), which could result in competitive advantage over other algae and in the ability to thrive at greater depths. The penetration of light into the water column in NCP is strongly limited by the presence of particulate material of terrestrial origin in the head zone (Huovinen et al, 2016), which will define the lower limit of distribution of foliose algae in sites where discharges are high (e.g., Barrett and Edgar, 2010). Indeed, the variation of substrate inclination, which influences the degree of sedimentation and light regimes, has been suggested to influence the co-occurrence patterns of macroalgae elsewhere (e.g., South Patagonia, Cárdenas and Montiel, 2015).…”
Section: Community Structure and Environmental Variability In Shallow Watersmentioning
confidence: 99%
“…The advantages include: reducing the time spent retrieving samples from the field and analysing them in the laboratory (although this is balanced by time spent processing imagery); generating a permanent record that can be revisited; an ability to sample a wider range of environments; and, perhaps most importantly, non-destructive sampling, thereby allowing sensitive benthic sites, including those within marine reserves, to be repeatedly sampled with minimal disturbance. Qualitative and quantitative data derived from imagery are used for multiple purposes, such as creating inventories or quantifying the biodiversity and community composition of an area [ 5 7 ], describing benthic habitats [ 8 , 9 ], documenting environmental deterioration due to anthropogenic or natural causes [ 2 , 10 12 ], interpretation or validation of remotely sensed data [ 13 – 16 ]; establishing relationships for predictive modelling [ 17 19 ]; and monitoring for change [ 3 , 20 , 21 ]. Thus, collection and interpretation of imagery has become a standard tool for sampling marine environments.…”
Section: Introductionmentioning
confidence: 99%
“…This previous study identified that salinity and depth were the primary drivers of both prokaryotic and eukaryotic microbiome diversity and composition changes, while oxygen and temperature only played a minor role in determining taxonomic patterns. However, other factors such as tannin induced light penetration decreases or grazing pressures may also play a role 16,17 , especially when there are differences between prokaryotic and eukaryotic community patterns. The depth and salinity effects are shown to be linked to primarily the LSL (low-salinity layer), with distinct diversity and community differences between Chalky Inlet (containing the smallest LSL) and Doubtful Sound (containing the largest LSL).…”
mentioning
confidence: 99%